Trapped with the Texan - Rock, Joanne (Texas Cattleman's Club: heir apparent, 2021)
"Valencia Donovan's plan to dazzle the wealthy investor she needs for her horse rescue start-up takes an unexpected turn when a tornado strands her with Lorenzo Cortez-Williams. Giving in to attraction in a desperate moment only makes them hungry for more. After they've blown away all boundaries, Valencia's treacherous feelings for the guarded ranching heir could jeopardize her lifelong dream. But closing the deal--while walking away from their intimate affair--could cost her even more..."--Back cover.